Odzivi socialnega dela na ukrepe za zajezitev epidemije covida-19 v domovih za stare ljudi - Mali, Jana (Socialno delo, 2022)
The first part of the article shows how the covid-19 epidemic revived ideas about the development of social work with old people. More frequent violations of human rights, increasing discrimination of old people, and searching for answers to the increasingly severe hardships of the social isolation of the old people – these are topics that call for the establishment of specialization for social work with old people. The development of specialized knowledge also benefits the development of social work in homes for old people. Some key practices for the development of new areas of social work in homes are shown. In the central part of the paper, research with social workers in Slovenian homes is described and the results of the epidemic's impact on social work are presented. The article presents the key challenges for social work, how social work maintains its role at organizing institutional care and what are the most pressing ethical dilemmas of social work. Both the shortcomings and advantages of social work are shown in order to recognize the existing risks for social work as an opportunity for further development of the profession.
Keywords: advocacy; anti-covid measures; dolgotrajna oskrba; ethical dilemmas; etične dileme; institucionalna oskrba; institutional care; long-term care; proticovidni ukrepi; social isolation; socialna izolacija; zagovorništvo